α-methylstyrene-assisted maleic anhydride grafted poly(lactic acid) as an effective compatibilizer affecting properties of microcrystalline cellulose/poly(lactic acid) composites - F. Y. Wang; L. Dai; T. T. Ge; C. B. Yue; Y. M. Song (eXPRESS Polymer Letters)
A new compatibilizer, maleic anhydride-grafted poly(lactic acid) (PLA-g-AMS/MAH), was synthesized for microcrystalline cellulose (MCC)/poly(lactic acid) (PLA) composites. PLA-g-AMS/MAH copolymer was prepared by freeradical melt grafting using α-Methylstyrene as a co-monomer and dicumyl peroxide (DCP) as a free-radical initiator. The molecular structure of the prepared PLA-g-AMS/MAH was characterized by Fourier transform infrared spectroscopy (FTIR), and the grafting degree (Dg) of PLA-g-AMS/MAH was studied by acid-alkali titration. The effects of the Dg of PLA-g-AMS/MAH on the rheological and mechanical properties of MCC/PLA composites were investigated. The results showed that MAH was successfully grafted onto PLA molecular chains and the Dg of PLA-g-AMS/MAH was dramatically higher than the Dg of PLA-g-MAH. At an AMS/MAH ratio of 2:1, the Dg value of the graft copolymer reached maximum. Additionally, the storage modulus, complex viscosity, equilibrium torque, and shear heat of the MCC/PLA composite melts increased with increased Dg of PLA-g-AMS/MAH. The mechanical properties of the MCC/PLA composites also were significantly improved after the addition of PLA-g-AMS/MAH copolymer.